The Role of Entrepreneurial Traits in Shaping Information Search Behaviors and SME Performance in Vietnam - Nguyen Thị Bı́ch Van (Journal of Management Practices, Humanities and Social Sciences, 2024)
Entrepreneurial traits are seen to be a crucial component of new venture survival. However, we only have a limited understanding of how individual entrepreneurs contribute to its emergence. Although it is sometimes asserted that curiosity plays a significant role in entrepreneurship, this notion is not well-supported by actual data. By investigating the connection between founders' entrepreneurial curiosity and corporate innovation, this study seeks to close this gap. We also investigate how this link is mediated by information search and moderated by competitive intelligence capability. By examining three waves of data gathered from 343 business owners, we discover that the curiosity, dynamism, and marketing of entrepreneurs are significantly correlated with their persistence and effort in finding information. Furthermore, our results demonstrate that information search effort mediates the influence of marketing, curiosity, and dynamism and that information search persistence mediates the effect of attributes on SME performance. Additionally, we discover that competitive intelligence capability moderates these connections.